2007
DOI: 10.1051/vetres:2007046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cellular responses toMycoplasma mycoidessubsp.mycoidessmall colony biotype associated with control of contagious bovine pleuropneumonia

Abstract: -A better understanding of protective immune memory against contagious bovine pleuropneumonia (CBPP) is needed in order to facilitate the development of safer vaccines based on selected components of the pathogen. For this purpose, cells collected from lymph nodes draining the lungs of Mycoplasma mycoides subsp. mycoides small colony biotype (MmmSC)-infected cattle were stimulated with the pathogen in vitro and evaluated concurrently for proliferation (CFSE based method), expression of activation, memory marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
2
25
0
1
Order By: Relevance
“…Previous work indicated that CD4 ϩ T cells make a major contribution to the vigorous T1-biased anamnestic cellular immune response observed for cattle that have recovered from infection (2,3,18). More recently, we demonstrated that MmmSC-specific memory CD4 ϩ T cells comprise two phenotypically and functionally different subsets (19).…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…Previous work indicated that CD4 ϩ T cells make a major contribution to the vigorous T1-biased anamnestic cellular immune response observed for cattle that have recovered from infection (2,3,18). More recently, we demonstrated that MmmSC-specific memory CD4 ϩ T cells comprise two phenotypically and functionally different subsets (19).…”
mentioning
confidence: 61%
“…ϩ T cells appear to be associated with resistance to infection (2,3,18), thus providing a rationale for targeting these responses in novel vaccine strategies. Ideally, subunit CBPP vaccines should elicit not only CD4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to assess an effective subunit vaccine against Mycoplasma mycoides subsp. mycoides, researchers are studying molecules able to activate central and effector memory CD4 + cells, since it seems they are the most suitable peptides to be included in such vaccines (Totté et al, 2008).…”
Section: Discussionmentioning
confidence: 99%